The Montpellier codex: part I: critical commentary: fascicles 1 and 2 - Tischler, Hans (Madison A-R Editions, 1978)
As a thorough revision of Rokseth's out-of-print edition of this monument of thirteenth-century polyphony, the present publication considers and lists all parallel versions. In addition the editor has made hundreds of corrections and additions in music and texts, provided several entirely new renditions, improved versifications and musica ficta, and added many other helpful features. This edition is published in four physical volumes: Part 1 (M2-3): Critical Commentar; Fascicles 1 and 2 : Part 2 (M4-5): Fascicles 3, 4, and 5 Part 3 (M6-7): Fascicles 6, 7, and 8 Part 4 (M8): Texts and Translation The final volume (M 8) of texts and translations, also includes an index of first lines, and pronunciation guides.